Regions of KCNQ K+ channels controlling functional expression - Choveau, Frank; Shapiro, Mark S. (Frontiers in Physiology, 2012)
KCNQ1-5 α-subunits assemble to form K+ channels that play critical roles in the function of numerous tissues. The channels are tetramers of subunits containing six transmembrane domains. Each subunit consists of a pore region (S5-pore-S6) and a voltage sensor domain (S1-S4). Despite similar structures, KCNQ2 and KCNQ3 homomers yield small current amplitudes compared to other KCNQ homomers and KCNQ2/3 heteromers. Two major mechanisms have been suggested as governing functional expression. The first involves control of channel trafficking to the plasma membrane by the distal part of the C-terminus, containing two coiled-coiled domains, required for channel trafficking and assembly. The proximal half of the C-terminus is the crucial region for channel modulation by signaling molecules such as calmodulin, which may mediate C- and N-terminal interactions. The N-terminus of KCNQ channels has also been postulated as critical for channel surface expression. The second mechanism suggests networks of interactions between the pore helix and the selectivity filter, and between the pore helix and the S6 domain that govern KCNQ current amplitudes. Here, we summarize the role of these different regions in expression of functional KCNQ channels.